Characterization of anti-interferon-γ antibodies in HIV-negative immunodeficient patients infected with unusual intracellular microorganisms. Issue 7 (April 2018) - Wipasa, Jiraprapa; Chaiwarith, Romanee; Chawansuntati, Kriangkrai; Praparattanapan, Jutarat; Rattanathammethee, Kritsadee; Supparatpinyo, Khuanchai
A major characteristic of immunodeficiency associated with life-threatening intracellular infection in adults is the presence of anti-interferon-γ antibodies. Although little is known about the mechanism underlying this syndrome, it is believed that the antibodies inhibit the activity of downstream signaling pathway of interferon-γ. In this study, the characteristics of these antibodies in patients who presented, or have a history of, intracellular infection and were positive to anti-interferon-γ antibodies were investigated. The antibodies exhibited mainly the IgG1 and the IgG4 subtypes and recognized the C-terminal of the interferon-γ linear epitope containing the KRKR motif, which is required for the biological activity of interferon-γ. The antibodies bound to recombinant interferon-γ with significantly lower avidity than antibodies to a recall antigen, tetanus toxoid, suggesting that the antibodies might have not undergone affinity maturation. The data from this study may provide fundamental information to better understand the properties of anti-interferon-γ antibodies, which can be useful for future studies. Impact statement: An increase in the number of immunodeficient patients related to autoantibodies to interferon (IFN)-γ has been observed particularly in East Asian adults. These patients are often presented with opportunistic infections caused by intracellular pathogens, including non-tuberculous mycobacteria (NTM), Cryptococcus neoformans, Penicillium marneffei (now called Talaromyces marneffei ), and non-typhoidal Salmonella spp. The mortality rate for this syndrome is relatively high with 32% patients dying at the median time of 25 months after diagnosis. Characterization of these autoantibodies may promote better understanding of the syndrome, an emerging health problem affecting East Asia populations and impeding their welfare and economic development.